Molybdenum-chromium-free low-alloy manganese silicon steel and heat treatment method thereof
Through the smelting and heat treatment process of molybdenum-free chromium-free low-alloy manganese silicon steel, the problem of high cost of power metal materials is solved, and high-performance power-connected metal materials are obtained, with low cost and excellent mechanical properties.
Patent Information
- Application Number
- CN202411636565.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-14
AI Technical Summary
Existing power metal materials contain expensive and resource-poor molybdenum and chromium elements, which leads to high production costs and high manufacturing costs. It is not suitable as power metal materials, which makes it difficult to promote and apply.
Using molybdenum-free chromium low alloy manganese silicon steel, steel scrap and electric furnace iron manganese are smelted, continuous casting, hot rolling, and austenitizing heat treatment and critical quenching treatment to obtain steel with excellent mechanical properties.
The manufacturing cost of steel materials for electric power tools has been reduced, and the performance of tensile strength greater than 750MPa, yield strength less than 505MPa, yield strength less than 0.8, and elongation greater than 25% has been obtained. It is suitable as a new generation of electric power connection tools material.
Smart Images

Figure CN119307815A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a low alloy manganese silicon steel and a heat treatment method thereof, in particular to a molybdenum-chromium-free low alloy manganese silicon steel and a heat treatment method thereof, belonging to the technical field of electric power hardware manufacturing. Background Art
[0002] Power fittings are key components that connect conductors and insulators, and their performance directly affects the normal and safe operation of the power grid. The main materials for power fittings are cast iron, aluminum alloy and steel. Among them, cast iron fittings are cheap and have simple production processes, but cast iron has poor toughness and is prone to impact fracture under complex working conditions; and although aluminum alloy power fittings have good oxidation resistance, their strength is low. In order to meet the requirements of use, the cross-sectional size must be increased, which significantly increases the manufacturing cost. CrMo alloy steel has excellent comprehensive properties and is one of the preferred materials for the new generation of connection hardware. CrMo alloy steel has high static strength, impact toughness and high fatigue limit, as well as good hardenability and forging formability. In particular, after a certain heat treatment, the mechanical properties of the material can be effectively improved.
[0003] In order to improve the material performance of power fittings, Chinese invention patent CN108359904A discloses a heat treatment method for improving the low-temperature brittleness of forged power fittings under extremely cold conditions. The components of the fittings include: carbon 0.32% to 0.45%, silicon 0.17% to 0.37%, manganese 0.40% to 0.80%, phosphorus not more than 0.025%, sulfur not more than 0.025%, chromium 0.80% to 1.20%, molybdenum 0.15% to 0.25%, nickel and copper total amount not more than 0.030%, the balance is Fe and unavoidable impurities; the method includes: S 1. Normalizing; S2. Heat the treated alloy steel parts to 500±10℃, keep warm for 30 minutes, then continue to heat to 850±10℃, keep warm for 90 minutes, and change from water quenching to oil quenching; S3. Heat the treated alloy steel parts to 550±10℃, keep warm for 120 minutes, temper, and cool in oil after removal from furnace; S4. Heat the treated alloy steel parts to 500±10℃, keep warm for 30 minutes, then continue to heat to 800±10℃, keep warm for 90 minutes, change from water quenching to oil quenching; S5. Heat the treated alloy steel parts to 640±10℃, keep warm for 120 minutes, and cool in oil after removal from furnace. After treatment, the room temperature and low temperature brittleness of alloy steel parts are significantly improved, meeting the requirements of long-term operation of power fittings in extremely cold climates.
[0004] Chinese invention patent CN1727509A also discloses an austenitic non-magnetic steel for electric power fittings and a preparation method thereof, wherein the non-magnetic steel contains 20-26% manganese, 2%-10% chromium, 1%-4% aluminum, 0.18%-0.24% carbon, 0.1%-0.2% rare earth elements, ≤0.04% sulfur, ≤0.04% phosphorus, and the remainder is iron.
[0005] The CrMo alloy steel in the above invention patent contains expensive molybdenum and chromium elements which are scarce in my country and have high production costs. The manufacturing cost of power fittings is high, making it unsuitable as a material for power fittings and difficult to promote and apply.
[0006] In this context, scientific and technological workers have improved the performance of steel by changing the steel rolling process and microalloying titanium and niobium. Chinese invention patent CN109023053A discloses a 600MPa grade multiphase steel with good flanging performance, whose components and wt% are: C: 0.060-0.100%, Si: 0.060-0.400%, Mn: 1.20-2.00%, P: 0.020% or less, S: 0.010% or less, Als: 0.015-0.070%, Cr: 0.15-0.35%, Ti: 0.010-0.035%, Nb: 0.010-0.035%, N: 0.006% or less; production process: cast billet after conventional smelting according to the composition setting; hot rolling process; cold rolling process; naturally cool to room temperature and standby. The yield strength reaches 360-440MPa, the tensile strength is 600-700MPa, the elongation is more than 19%, and the hole expansion rate is more than 45%; its microstructure is pearlite, bainite, ferrite and a small amount of martensite and residual austenite structure, thus ensuring that it has high strength while also having good forming performance, flanging performance and collision energy absorption performance.
[0007] Chinese invention patent CN101880823A also discloses a hot-rolled niobium microalloyed multiphase steel and its preparation method, which involves the preparation of high-strength and high-plasticity hot-rolled low-alloy steel. The preparation steps are: heating the low-silicon Al-Si-Mn-Nb steel to an austenitizing temperature in the range of 1250-1350°C and keeping it warm so that niobium is completely dissolved in austenite, then cooling it to a temperature in the range of 1250-1100°C at a speed of 5°C / s-20°C / s, and heating it for 0.1-10s. -1 The strain rate is 1-4 times of deformation, and the strain amount is controlled at 10%-50%, and then cooled to A at a cooling rate C2 of 5℃ / s-50℃ / s. 3 To Ar 3 Within this temperature range, the -1 ~30s -1 The steel is subjected to 1 to 4 deformations at a strain rate of 100°C, and the interval time and deformation amount of each pass are controlled. After generating ferrite with a volume fraction of 30 to 60%, the steel is immediately cooled to a bainite transformation zone within the range of 400 to 500°C at a rate of 10 to 50°C / s for isothermal treatment. The yield strength of the hot-rolled niobium microalloyed multiphase steel prepared by the invention is higher than 500MPa, the tensile strength is higher than 800MPa, and the elongation is higher than 30%.
[0008] However, niobium is expensive, and titanium is easily oxidized. When added to steel, it is easy to generate low-density TiO 2 Inclusions, which remain in the steel, reduce the strength and toughness of the steel, causing the properties of the steel to fluctuate drastically. Summary of the invention
[0009] The present invention aims to reduce the manufacturing cost of steel materials for electric power fittings and to provide a molybdenum-chromium-free low-alloy manganese-silicon steel and a heat treatment method thereof. The molybdenum-chromium-free low-alloy manganese-silicon steel has low cost and excellent comprehensive mechanical properties.
[0010] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A molybdenum-chromium-free low-alloy manganese-silicon steel comprises, by mass percentage, 78-80% of automobile steel, 17-19% of scrap steel, 1.3-1.4% of ferrosilicon and 1.6-1.7% of electric furnace ferromanganese.
[0011] A further improvement of the present invention is that the automobile steel comprises, by mass percentage, 0.08-0.21% C, 0.15-0.30% Si, 1.29-1.58% Mn, P≤0.030%, S≤0.025%, Al≥0.015%, 0.16-0.29% Zn, and the balance is Fe and unavoidable impurities.
[0012] A further improvement of the present invention is that the scrap steel comprises, by mass percentage, 0.14-0.22% C, 0.30-0.65% Mn, Si≤0.30%, S≤0.050%, P≤0.045%, and the balance is Fe and unavoidable impurities.
[0013] A further improvement of the present invention is that the ferrosilicon comprises, by mass percentage, 74.82-75.77% Si, Al≤0.5%, Ca≤1.0%, Mn≤0.4%, P≤0.035%, S≤0.02%, C≤0.1%, and the balance is Fe and unavoidable impurities.
[0014] A further improvement of the present invention is that the electric furnace ferromanganese comprises 89.86-90.61% Mn, C≤0.10%, Si≤1.0%, P≤0.05%, S≤0.02% by mass, and the balance is Fe and unavoidable impurities.
[0015] A further improvement of the present invention is that the tensile strength of the molybdenum-chromium-free low-alloy manganese-silicon steel is greater than 750MPa, the yield strength is less than 505MPa, the yield strength ratio is less than 0.8, and the elongation is greater than 25%.
[0016] A heat treatment method for molybdenum-chromium-free low-alloy manganese-silicon steel comprises the following steps: After the scrap steel is melted, the temperature is raised to 1605-1628°C, and then preheated automobile steel is added. After the automobile steel is melted, preheated ferrosilicon and electric furnace ferromanganese are added. After the ferrosilicon and electric furnace ferromanganese are melted, molten steel is obtained; The molten steel is heated to 1663-1679°C, and then the multi-element alloy wire is fed into the molten steel, and then the slag is removed, the steel is allowed to stand, and the steel is cooled to form a steel billet; hot rolling the steel billet into steel plates; The steel plate is subjected to austenitizing heat treatment, and then to critical quenching treatment after water cooling quenching.
[0017] A further improvement of the present invention is that the automobile steel is preheated at a temperature of 550-600° C. for a time of 90-120 minutes.
[0018] A further improvement of the present invention is that the preheating temperature of ferrosilicon and electric furnace ferromanganese is 880-960° C. and the preheating time is 60-80 minutes.
[0019] A further improvement of the present invention is that the multi-element alloy wire comprises, by mass percentage, 31.47-32.73% Al, 7.84-8.07% Ba, 3.15-3.76% Mg, 5.12-5.79% Ce, 6.22-6.84% Ca, 6.38-6.81% K, 15.80-17.17% Si, S<0.035%, P<0.040%, and the remainder is Fe and unavoidable impurities.
[0020] A further improvement of the present invention is that the diameter of the multi-element alloy wire is 5-6 mm.
[0021] A further improvement of the present invention is that the multi-element alloy wire is inserted into the lower part of the molten steel.
[0022] A further improvement of the present invention is that the amount of the multi-element alloy wire added is 0.6-0.7% of the mass of the molten steel.
[0023] A further improvement of the present invention is that the temperature after cooling is 1527-1542°C.
[0024] A further improvement of the present invention is that the thickness of the steel billet is 60-70 mm.
[0025] A further improvement of the present invention is that the hot rolling temperature is 1120-1150° C. and the time is 120-150 minutes.
[0026] A further improvement of the present invention is that the temperature of the austenitizing heat treatment is 900° C. and the time is 60-90 min.
[0027] A further improvement of the present invention is that the critical quenching treatment conditions are: keeping at 720°C for 40-60 min, cooling to room temperature with water, and then keeping at 680°C for 100-120 min.
[0028] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses automobile steel as the main raw material, and adds an appropriate amount of scrap steel and a small amount of cheap ferrosilicon and electric furnace ferromanganese. It does not contain expensive alloy elements such as molybdenum, nickel, vanadium, niobium, and does not contain chromium, which is scarce in my country, and has low production cost. The present invention obtains molybdenum-chromium-free low-alloy manganese-silicon steel with excellent performance through molten steel smelting, continuous casting, hot rolling and heat treatment. The production process is simple and the production efficiency is high. The ferrosilicon and electric furnace ferromanganese used in the present invention are to increase the silicon content and manganese content in the steel, and to improve the strength of the molybdenum-chromium-free low-alloy steel by using the solid solution strengthening effect of silicon and manganese elements.
[0029] Furthermore, Al, Ba, Mg, Ce and K in the multi-element alloy wire have excellent deoxidation and inclusion removal effects, especially Mg and K, which have excellent desulfurization effects in addition to excellent deoxidation effects. Ca is beneficial to improving the morphology of inclusions. Adding multi-element alloy wire accounting for 0.6~0.7% of the mass fraction of molten steel entering the ladle is beneficial to the purification of molten steel and the improvement of the mechanical properties of steel.
[0030] Furthermore, the critical quenching treatment is to obtain a dual-phase structure of ferrite and martensite. A lower temperature will result in excessive ferrite, and a higher temperature will result in too high a martensite content, so the two-phase region temperature is selected to be 720°C.
[0031] The molybdenum-chromium-free low-alloy manganese-silicon steel of the present invention has excellent comprehensive mechanical properties, a tensile strength greater than 750MPa, a yield strength less than 505MPa, a yield strength ratio less than 0.8, and an elongation greater than 25%. It is an important alternative material for a new generation of power connection fittings and has good prospects for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a heat treatment process diagram of the molybdenum-chromium-free low-alloy manganese-silicon steel in the present invention. DETAILED DESCRIPTION
[0033] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.
[0034] See also Figure 1The pretreatment method of the molybdenum-chromium-free low-alloy manganese-silicon steel of the present invention uses cheap scrap automobile steel SAPH440 (the chemical composition and mass percentage of the scrap automobile steel SAPH440 are: 0.08-0.21% C, 0.15-0.30% Si, 1.29-1.58% Mn, P≤0.030%, S≤0.025%, Al≥0.015%, 0.16-0.29% Zn, and the balance is Fe and unavoidable impurities) as the main raw material, and adds an appropriate amount of Q235 scrap steel (the chemical composition and mass percentage of the Q235 scrap steel are: 0.14-0.22% C, 0.30- 0.65%Mn, Si≤0.30%, S≤0.050%, P≤0.045%, the balance is Fe and inevitable impurities) and a small amount of cheap ferrosilicon (the chemical composition and mass percentage of the ferrosilicon are: 74.82-75.77%Si, ≤0.5%Al, ≤1.0%Ca, Mn≤0.4%, P≤0.035%, S≤0.02%, C≤0.1%, the balance is Fe and inevitable impurities) and electric furnace ferromanganese (the chemical composition and mass percentage of the electric furnace ferromanganese are: 89.86-90.61%Mn, C≤0.10%, Si≤1.0%, P≤0.05%, S≤0.02%, the balance is Fe and inevitable impurities), through smelting, continuous casting, hot rolling and heat treatment, to obtain molybdenum-chromium-free low-alloy manganese-silicon steel with excellent performance, which is an important alternative material for the new generation of power connection hardware.
[0035] The specific heat treatment method includes the following steps: ① Use medium frequency induction furnace to melt molten steel. The steelmaking charge is composed of 78-80% by mass of scrap automobile steel SAPH440, 17-19% by mass of Q235 scrap steel, 1.3-1.4% by mass of ferrosilicon and 1.6-1.7% by mass of electric furnace ferromanganese. The total mass fraction of the steelmaking charge is 100%. During the molten steel melting process, 17-19% by mass of Q235 scrap steel is first put into the furnace for heating. After all the Q235 scrap steel is melted, the temperature is raised to 1605-1628℃. Then add 78-80% by mass of scrap automobile steel SAPH440 preheated at 550-600℃ for 90-120 minutes; after all the scrap automobile steel SAPH440 is melted, add 1.3-1.4% by mass of ferrosilicon and 1.6-1.7% by mass of electric furnace ferromanganese preheated at 880-960℃ for 60-80 minutes in sequence; after all the ferrosilicon and electric furnace ferromanganese are melted, heat the molten steel in the furnace to 1663-1679℃, and then discharge the molten steel into the ladle; ② After all the molten steel in the furnace enters the ladle, the multi-element alloy wire is fed into the molten steel with a wire feeder, and the multi-element alloy wire is inserted into the lower part of the molten steel in the ladle, and the head of the multi-element alloy wire is 60~80 mm away from the bottom of the ladle; the chemical composition and mass percentage of the multi-element alloy wire are: 31.47-32.73% Al, 7.84-8.07% Ba, 3.15-3.76% Mg, 5.12-5.79% Ce, 6.22-6.84% Ca, 6.38-6.81% K, 15.80-17.17% Si, <0.035% S, <0.040% P, and the remainder is Fe and unavoidable impurities; the diameter of the multi-element alloy wire is φ5~6 mm; the amount of multi-element alloy wire added accounts for 0.6~0.7% of the mass of the molten steel entering the ladle; ③ After the molten steel in the ladle is slag-stripped and left to stand, when the temperature drops to 1527-1542℃, the molten steel is directly cast into a 60-70mm thick billet on the continuous casting machine; then the billet is heated to 1120-1150℃, kept warm for 120-150 minutes, and then directly rolled into a 20-50 mm steel plate on the hot rolling mill; ④ Use a box-type resistance furnace or a pit-type resistance furnace for heat treatment; first, reheat the steel plate in step ③ to 900℃, keep it warm for 60-90 min for complete austenitization heat treatment, obtain a lath-shaped martensite structure after water-cooling quenching, and then perform critical quenching treatment; in order to obtain a ferrite and martensite dual-phase structure, select the two-phase region temperature of 720℃, heat the steel plate to 720℃ in the two-phase region and keep it warm for 40-60 min, then water-cool it to room temperature; finally, heat it to 680℃ and keep it warm for 100-120 min for tempering treatment, and you can get a molybdenum-chromium-free low-alloy manganese-silicon steel with excellent performance.
[0036] The present invention adopts a medium frequency induction furnace to melt molten steel, which has a simple process and a high alloy element yield. The sulfur and phosphorus content of the main furnace charge, the scrap automobile steel SAPH440, is very low. In addition, in order to improve the corrosion resistance of automobile steel, before the automobile steel plate is used, it is necessary to plate a metal zinc with a thickness of 5-10 um on the surface of the steel plate, so the scrap automobile steel SAPH440 contains 0.16-0.29% Zn. Zinc is an important alloying element. Zinc can improve the mechanical properties of steel, improve the toughness and plasticity of steel, and also enhance the corrosion resistance of steel. However, if the scrap automobile steel SAPH440 is directly heated in the furnace, the zinc element is very easy to oxidize and burn, and the advantages of the zinc element in improving the mechanical properties of steel and improving the toughness and plasticity of steel cannot be brought into play. The present invention adds 78-80% of the mass fraction of scrap automobile steel SAPH440, and also adds 17-19% of Q235 scrap steel. During the molten steel smelting process, Q235 scrap steel with a mass fraction of 17-19% is first heated in the furnace. After all the Q235 scrap steel is melted, the temperature is raised to 1605-1628℃, and then 78-80% scrap automobile steel SAPH440 preheated at 550-600℃ for 90-120 minutes is added. 78-80% scrap automobile steel SAPH440 preheated at 550-600℃ for 90-120 minutes is directly added to the 1605-1628℃ Q235 molten steel. Scrap automobile steel SAPH440 is easy to melt, and the zinc, manganese, aluminum and other elements in the steel are less oxidized and burned, and the recovery rate of zinc, manganese, aluminum and other elements is high.
[0037] In the present invention, after all the scrap automobile steel SAPH440 is melted, 1.3-1.4% ferrosilicon and 1.6-1.7% electric furnace ferromanganese, which are preheated at 880-960°C for 60-80 minutes, are added in sequence. The purpose of adding 1.3-1.4% ferrosilicon and 1.6-1.7% electric furnace ferromanganese is to increase the silicon content and manganese content in the steel, and to improve the strength of the molybdenum-chromium-free low-alloy steel by the solid solution strengthening effect of silicon and manganese elements. After all the ferrosilicon and electric furnace ferromanganese are melted, the molten steel in the furnace is heated to 1663-1679°C, and then the molten steel is discharged from the furnace to the ladle. The present invention uses 78-80% of the scrap automobile steel SAPH440 and 17-19% of the Q235 scrap steel as the main steelmaking raw materials, and the cost is low. However, the oxygen content in the molten steel after melting is high, there are many inclusions, and the solidification structure of the steel is coarse, which seriously affects the performance of the steel plate after casting. After all the molten steel in the furnace enters the ladle, a wire feeder is used to feed the multi-element alloy wire into the molten steel, and the multi-element alloy wire is inserted into the lower part of the molten steel in the ladle, and the head of the multi-element alloy wire is 60-80 mm away from the bottom of the ladle; the chemical composition and mass fraction of the multi-element alloy wire are: 31.47-32.73% Al, 7.84-8.07% Ba, 3.15-3.76% Mg, 5.12-5.79% Ce, 6.22-6.84% Ca, 6.38-6.81% K, 15.80-17.17% Si, <0.035% S, <0.040% P, and the remainder is Fe and inevitable impurities; the diameter of the multi-element alloy wire is φ5-6 mm; and the amount of the multi-element alloy wire added accounts for 0.6-0.7% of the mass of the molten steel entering the ladle. The main purpose of adding multi-element alloy wire in the present invention is to utilize 31.47-32.73% Al, 7.84-8.07% Ba, 3.15-3.76% Mg, 5.12-5.79% Ce and 6.38-6.81% K added to the multi-element alloy wire, which has excellent deoxidation and inclusion removal effects, especially the addition of 3.15-3.76% Mg and 6.38-6.81% K, which have excellent desulfurization effects in addition to excellent deoxidation effects. The addition of 6.22-6.84% Ca is also beneficial to improving the morphology of inclusions. Adding multi-element alloy wire accounting for 0.6-0.7% of the mass fraction of molten steel entering the ladle is beneficial to the purification of molten steel and the improvement of the mechanical properties of steel.
[0038] After the molten steel in the ladle of the present invention is deslagging and standing, when the temperature drops to 1527-1542°C, the molten steel is directly cast into a steel billet with a thickness of 60-70 mm on a continuous casting machine; then the steel billet is heated to 1120-1150°C, kept warm for 120-150 minutes, and then directly rolled into a steel plate of 20-50 mm on a hot rolling mill. The as-cast steel plate contains many Widmanstatten structures, which reduce the comprehensive mechanical properties of the steel plate, and heat treatment is required to improve the structure and performance of the steel plate. The present invention uses a box-type resistance furnace or a pit-type resistance furnace for heat treatment; first, the cast steel plate is reheated to 900°C, kept warm for 60-90 min for complete austenitization heat treatment to eliminate the Widmanstatten structure, and after water-cooling quenching, a martensitic structure with fine size and high dislocation density is obtained, which has high strength but low toughness. Then, the two-phase critical quenching treatment is carried out. In order to obtain the two-phase structure of ferrite and martensite, an appropriate temperature should be set. A lower temperature will lead to excessive ferrite, and a higher temperature will result in too high martensite content. The two-phase temperature is selected to be 720℃. The steel plate is heated to 720℃ and kept in the two-phase zone for 40-60 min and then water-cooled to room temperature; finally, it is heated to 680℃ and kept for 100-120 min for tempering treatment to obtain molybdenum-chromium-free low-alloy manganese-silicon steel with excellent performance.
[0039] The following are specific embodiments.
[0040] Example 1 The heat treatment method of molybdenum-chromium-free low-alloy manganese-silicon steel is obtained by smelting, continuous casting, hot rolling and heat treatment, using cheap scrap automobile steel SAPH440 as the main raw material, adding an appropriate amount of Q235 scrap steel and a small amount of cheap ferrosilicon and electric furnace ferromanganese. The specific preparation process steps are as follows: ① A medium frequency induction furnace is used to melt molten steel. The steelmaking charge is composed of 78% by mass of scrap automobile steel SAPH440 (the chemical composition and mass fraction of the scrap automobile steel SAPH440 are: 0.08% C, 0.30% Si, 1.29% Mn, 0.021% P, 0.016% S, 0.018% Al, 0.16% Zn, and the balance is Fe and unavoidable impurities), 19% Q235 scrap steel (the The chemical composition and mass fraction of Q235 scrap steel are: 0.14% C, 0.65% Mn, 0.24% Si, 0.047% S, 0.041% P, the balance is Fe and unavoidable impurities), 1.3% ferrosilicon (the chemical composition and mass fraction of the ferrosilicon are: 74.82% Si, 0.28% Al, 0.55% Ca, 0.13% Mn, 0.026% P, 0.008% S, 0.07% C, the balance is Fe and inevitable impurities) and 1.7% electric furnace ferromanganese (the chemical composition and mass fraction of the electric furnace ferromanganese are: 89.86% Mn, 0.07% C, 0.68% Si, 0.038% P, 0.009% S, the balance is Fe and inevitable impurities), the total mass fraction of the charge is 100%; during the molten steel smelting process, firstly, 19% Q235 scrap steel is put into the furnace for heating; Q235 scrap steel After all the steel is melted, the temperature is raised to 1605℃; then 78% scrap automobile steel SAPH440 preheated at 550℃ for 120 minutes is added; after all the scrap automobile steel SAPH440 is melted, 1.3% ferrosilicon and 1.7% electric furnace ferromanganese preheated at 880℃ for 80 minutes are added in sequence; after all the ferrosilicon and electric furnace ferromanganese are melted, the molten steel in the furnace is heated to 1663℃, and then the molten steel is discharged into the ladle; ② After all the molten steel in the furnace enters the ladle, the multi-element alloy wire is fed into the molten steel with a wire feeder, and the multi-element alloy wire is inserted into the lower part of the molten steel in the ladle, and the head of the multi-element alloy wire is 60 mm away from the bottom of the ladle; the chemical composition and mass fraction of the multi-element alloy wire are: 31.47% Al, 8.07% Ba, 3.15% Mg, 5.79% Ce, 6.22% Ca, 6.81% K, 15.80% Si, 0.032% S, 0.027% P, and the remainder is Fe and unavoidable impurities; the diameter of the multi-element alloy wire is φ5 mm; the amount of multi-element alloy wire added accounts for 0.6% of the mass fraction of the molten steel entering the ladle; ③ After the molten steel in the ladle is slag-stripped and left to stand, when the temperature drops to 1527℃, the molten steel is directly cast into a 60mm thick billet on the continuous casting machine; then the billet is heated to 1120℃, kept warm for 150 minutes, and then directly rolled into a 20mm steel plate on the hot rolling mill; ④ Use a box-type resistance furnace or a pit-type resistance furnace for heat treatment; first, reheat the steel plate in step ③ to 900℃, keep it warm for 60 min for complete austenitization heat treatment, obtain a lath-shaped martensite structure after water-cooling quenching, and then perform critical quenching treatment; in order to obtain a ferrite and martensite dual-phase structure, the two-phase region temperature is selected as 720℃, the steel plate is heated to 720℃ and kept warm for 40 min in the two-phase region, and then water-cooled to room temperature; finally, heat it to 680℃ and keep it warm for 100 min for tempering treatment, and excellent performance of molybdenum-chromium-free low-alloy manganese-silicon steel can be obtained, and its mechanical properties are shown in Table 1.
[0041] Example 2 The heat treatment method of molybdenum-chromium-free low-alloy manganese-silicon steel is obtained by smelting, continuous casting, hot rolling and heat treatment, using cheap scrap automobile steel SAPH440 as the main raw material, adding an appropriate amount of Q235 scrap steel and a small amount of cheap ferrosilicon and electric furnace ferromanganese. The specific preparation process steps are as follows: ① A medium frequency induction furnace is used to melt molten steel. The steelmaking charge is composed of 80% by mass of scrap automobile steel SAPH440 (the chemical composition and mass fraction of the scrap automobile steel SAPH440 are: 0.21% C, 0.15% Si, 1.58% Mn, 0.022% P, 0.021% S, 0.016% Al, 0.29% Zn, and the balance is Fe and unavoidable impurities), 17% Q235 scrap steel (the The chemical composition and mass fraction of the Q235 scrap steel are: 0.22% C, 0.30% Mn, 0.18% Si, 0.040% S, 0.028% P, the balance is Fe and unavoidable impurities), 1.4% ferrosilicon (the chemical composition and mass fraction of the ferrosilicon are: 75.77% Si, 0.18% Al, 0.39% Ca, 0.26% Mn, 0.031% P, 0.015% S, 0.06 %C, the balance is Fe and inevitable impurities) and 1.6% electric furnace ferromanganese (the chemical composition and mass fraction of the electric furnace ferromanganese are: 90.61%Mn, 0.08%C, 0.84%Si, 0.045%P, 0.011%S, the balance is Fe and inevitable impurities), the total mass fraction of the charge is 100%; during the molten steel smelting process, firstly put 17% of Q235 scrap steel into the furnace for heating; Q235 After all the scrap steel is melted, the temperature is raised to 1628℃; then 80% of scrap automobile steel SAPH440 preheated at 600℃ for 90 minutes is added; after all the scrap automobile steel SAPH440 is melted, 1.4% of ferrosilicon and 1.6% of electric furnace ferromanganese preheated at 960℃ for 60 minutes are added in sequence; after all the ferrosilicon and electric furnace ferromanganese are melted, the molten steel in the furnace is heated to 1679℃, and then the molten steel is discharged into the ladle; ② After all the molten steel in the furnace enters the ladle, the multi-element alloy wire is fed into the molten steel with a wire feeder, and the multi-element alloy wire is inserted into the lower part of the molten steel in the ladle, and the head of the multi-element alloy wire is 80 mm away from the bottom of the ladle; the chemical composition and mass fraction of the multi-element alloy wire are: 32.73% Al, 7.84% Ba, 3.76% Mg, 5.12% Ce, 6.84% Ca, 6.38% K, 17.17% Si, 0.033% S, 0.029% P, and the remainder is Fe and unavoidable impurities; the diameter of the multi-element alloy wire is φ6 mm; the amount of multi-element alloy wire added accounts for 0.7% of the mass fraction of the molten steel entering the ladle; ③ After the molten steel in the ladle is slag-stripped and left to stand, when the temperature drops to 1542℃, the molten steel is directly cast into a 70mm thick billet on the continuous casting machine; then the billet is heated to 1150℃, kept warm for 120 minutes, and then directly rolled into a 50mm steel plate on the hot rolling mill; ④ Use a box-type resistance furnace or a pit-type resistance furnace for heat treatment; first, reheat the steel plate in step ③ to 900℃, keep it warm for 90 min for complete austenitization heat treatment, obtain a lath-shaped martensite structure after water-cooling quenching, and then perform critical quenching treatment; in order to obtain a ferrite and martensite dual-phase structure, the two-phase region temperature is selected as 720℃, the steel plate is heated to 720℃ in the two-phase region and kept warm for 60 min, and then water-cooled to room temperature; finally, heat it to 680℃ and keep it warm for 120 min for tempering treatment, and excellent performance of molybdenum-chromium-free low-alloy manganese-silicon steel can be obtained, and its mechanical properties are shown in Table 1.
[0042] Example 3 The heat treatment method of molybdenum-chromium-free low-alloy manganese-silicon steel is obtained by smelting, continuous casting, hot rolling and heat treatment, using cheap scrap automobile steel SAPH440 as the main raw material, adding an appropriate amount of Q235 scrap steel and a small amount of cheap ferrosilicon and electric furnace ferromanganese. The specific preparation process steps are as follows: ① A medium frequency induction furnace is used to melt molten steel. The steelmaking charge is composed of 79% by mass of scrap automobile steel SAPH440 (the chemical composition and mass fraction of the scrap automobile steel SAPH440 are: 0.13% C, 0.19% Si, 1.44% Mn, 0.022% P, 0.021% S, 0.019% Al, 0.24% Zn, and the balance is Fe and unavoidable impurities), 18% Q235 scrap steel (the Q The chemical composition and mass fraction of 235 scrap steel are: 0.17% C, 0.45% Mn, 0.25% Si, 0.041% S, 0.043% P, the balance is Fe and unavoidable impurities), 1.35% ferrosilicon (the chemical composition and mass fraction of the ferrosilicon are: 74.91% Si, 0.28% Al, 0.75% Ca, 0.18% Mn, 0.034% P, 0.009% S, 0.07% C , the balance is Fe and inevitable impurities) and 1.65% electric furnace ferromanganese (the chemical composition and mass fraction of the electric furnace ferromanganese are: 90.28%Mn, 0.08%C, 0.83%Si, 0.042%P, 0.006%S, the balance is Fe and inevitable impurities), the total mass fraction of the charge is 100%; during the molten steel smelting process, Q235 scrap steel with a mass fraction of 18% is first put into the furnace for heating; Q235 scrap steel After all the steel is melted, the temperature is raised to 1616°C; then, 79% scrap automobile steel SAPH440 preheated at 580°C for 100 minutes is added; after all the scrap automobile steel SAPH440 is melted, 1.35% ferrosilicon and 1.65% electric furnace ferromanganese preheated at 920°C for 70 minutes are added in sequence; after all the ferrosilicon and electric furnace ferromanganese are melted, the molten steel in the furnace is heated to 1672°C, and then the molten steel is discharged from the furnace into the ladle; ② After all the molten steel in the furnace enters the ladle, the multi-element alloy wire is fed into the molten steel with a wire feeder, and the multi-element alloy wire is inserted into the lower part of the molten steel in the ladle, and the head of the multi-element alloy wire is 70 mm away from the bottom of the ladle; the chemical composition and mass percentage of the multi-element alloy wire are: 31.80% Al, 7.94% Ba, 3.62% Mg, 5.48% Ce, 6.76% Ca, 6.51% K, 15.94% Si, 0.034% S, 0.037% P, and the remainder is Fe and unavoidable impurities; the diameter of the multi-element alloy wire is φ6 mm; the amount of multi-element alloy wire added accounts for 0.65% of the mass fraction of the molten steel entering the ladle; ③ After the molten steel in the ladle is slag-stripped and left to stand, when the temperature drops to 1539℃, the molten steel is directly cast into a 65mm thick billet on the continuous casting machine; then the billet is heated to 1130℃, kept warm for 140 minutes, and then directly rolled into a 35mm steel plate on the hot rolling mill; ④ Use a box-type resistance furnace or a pit-type resistance furnace for heat treatment; first, reheat the steel plate in step ③ to 900℃, keep it warm for 70 min for complete austenitization heat treatment, obtain a lath-shaped martensite structure after water-cooling quenching, and then perform critical quenching treatment; in order to obtain a ferrite and martensite dual-phase structure, the two-phase region temperature is selected as 720℃, the steel plate is heated to 720℃ and kept warm for 50 min in the two-phase region, and then water-cooled to room temperature; finally, heat it to 680℃ and keep it warm for 110 min for tempering treatment, and excellent performance of molybdenum-chromium-free low-alloy manganese-silicon steel can be obtained, and its mechanical properties are shown in Table 1.
[0043] Table 1 Mechanical properties of molybdenum-chromium-free low-alloy manganese-silicon steel
[0044] It can be seen from Table 1 that the tensile strength of the present invention is greater than 750 MPa, the yield strength is less than 505 MPa, the yield strength ratio is less than 0.8, and the elongation is greater than 25%.
[0045] The present invention uses cheap scrap automobile steel SAPH440 as the main raw material, and adds an appropriate amount of Q235 scrap steel and a small amount of cheap ferrosilicon and electric furnace ferromanganese. It does not contain expensive alloy elements such as molybdenum, nickel, vanadium, niobium, and does not contain chromium, which is scarce in my country, and has low production cost. The present invention obtains molybdenum-chromium-free low-alloy manganese silicon steel with excellent performance through molten steel smelting, continuous casting, hot rolling and heat treatment. The production process is simple and the production efficiency is high. The molybdenum-chromium-free low-alloy manganese silicon steel of the present invention has excellent comprehensive mechanical properties, a tensile strength greater than 750MPa, a yield strength less than 505MPa, a yield strength ratio less than 0.8, and an elongation greater than 25%. It is an important alternative material for a new generation of power connection hardware and has a good prospect for promotion and application.
[0046] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.
[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
Claims
1. A molybdenum-chromium-free low-alloy manganese-silicon steel, characterized in that: In terms of mass percentage, it includes 78-80% automotive steel, 17-19% scrap steel, 1.3-1.4% ferrosilicon and 1.6-1.7% electric furnace ferromanganese.
2. The molybdenum-chromium-free low-alloy manganese-silicon steel according to claim 1, characterized in that: Automobile steel, calculated by mass percentage, includes 0.08-0.21% C, 0.15-0.30% Si, 1.29-1.58% Mn, P≤0.030%, S≤0.025%, Al≥0.015%, 0.16-0.29% Zn, and the balance is Fe and unavoidable impurities.
3. The molybdenum-chromium-free low-alloy manganese-silicon steel according to claim 1, characterized in that: The scrap steel comprises, by mass percentage, 0.14-0.22% C, 0.30-0.65% Mn, Si≤0.30%, S≤0.050%, P≤0.045%, and the balance is Fe and unavoidable impurities.
4. The molybdenum-chromium-free low-alloy manganese-silicon steel according to claim 1, characterized in that: Ferrosilicon comprises 74.82-75.77% Si by mass percentage, Al≤0.5%, Ca≤1.0%, Mn≤0.4%, P≤0.035%, S≤0.02%, C≤0.1%, and the balance is Fe and unavoidable impurities.
5. The molybdenum-chromium-free low-alloy manganese-silicon steel according to claim 1, characterized in that: Electric furnace ferromanganese includes 89.86-90.61% Mn by mass percentage, C≤0.10%, Si≤1.0%, P≤0.05%, S≤0.02%, and the balance is Fe and unavoidable impurities.
6. The molybdenum-chromium-free low-alloy manganese-silicon steel according to claim 1, characterized in that: The tensile strength of molybdenum-chromium-free low-alloy manganese-silicon steel is greater than 750MPa, the yield strength is less than 505MPa, the yield strength ratio is less than 0.8, and the elongation is greater than 25%.
7. A heat treatment method for the molybdenum-chromium-free low-alloy manganese-silicon steel according to any one of claims 1 to 5, characterized in that: The following steps are involved: After the scrap steel is melted, the temperature is raised to 1605-1628°C, and then preheated automobile steel is added. After the automobile steel is melted, preheated ferrosilicon and electric furnace ferromanganese are added. After the ferrosilicon and electric furnace ferromanganese are melted, molten steel is obtained; The molten steel is heated to 1663-1679℃, and then the multi-element alloy wire is fed into the molten steel, and then the slag is removed, the steel is allowed to stand, and the steel is cooled to form a steel billet; hot rolling the steel billet into steel plates; The steel plate is subjected to austenitizing heat treatment, and then to critical quenching treatment after water cooling quenching.
8. The heat treatment method of molybdenum-chromium-free low-alloy manganese-silicon steel according to claim 7, characterized in that: The preheating temperature of automotive steel is 550-600℃ and the time is 90-120 minutes.
9. The heat treatment method of molybdenum-chromium-free low-alloy manganese-silicon steel according to claim 7, characterized in that: The preheating temperature of ferrosilicon and electric furnace ferromanganese is 880-960℃ and the time is 60-80 minutes.
10. The heat treatment method of molybdenum-chromium-free low-alloy manganese-silicon steel according to claim 7, characterized in that: The multi-element alloy wire comprises, by mass percentage, 31.47-32.73% Al, 7.84-8.07% Ba, 3.15-3.76% Mg, 5.12-5.79% Ce, 6.22-6.84% Ca, 6.38-6.81% K, 15.80-17.17% Si, S <0.035%, P <0.040%, and the balance is Fe and unavoidable impurities.
11. The heat treatment method of molybdenum-chromium-free low-alloy manganese-silicon steel according to claim 7, characterized in that: The amount of multi-element alloy wire added is 0.6~0.7% of the mass of molten steel.
12. The heat treatment method of molybdenum-chromium-free low-alloy manganese-silicon steel according to claim 7, characterized in that: The temperature after cooling is 1527-1542℃.
13. The heat treatment method of molybdenum-chromium-free low-alloy manganese-silicon steel according to claim 7, characterized in that: The thickness of the steel billet is 60-70mm.
14. The heat treatment method of molybdenum-chromium-free low-alloy manganese-silicon steel according to claim 7, characterized in that: The hot rolling temperature is 1120-1150°C and the time is 120-150 minutes.
15. The heat treatment method of molybdenum-chromium-free low-alloy manganese-silicon steel according to claim 7, characterized in that: The austenitizing heat treatment temperature is 900°C and the time is 60-90 min.
16. The heat treatment method of molybdenum-chromium-free low-alloy manganese-silicon steel according to claim 7, characterized in that: The critical quenching treatment conditions are: keep at 720℃ for 40-60 min, cool to room temperature with water, and then keep at 680℃ for 100-120 min.
Citation Information
Patent Citations
Hot rolled niobium micro-alloyed multi-phase steel and preparation method thereof
CN101880823A
Heat treatment method for improving low temperature brittleness of forged electric power fitting in extremely cold condition
CN108359904A
600 MPa grade multiphase steel with good flanging performance and production method thereof
CN109023053A
Austenitic nonmagnetic steel, and preparation method
CN1727509A